Origins and Development of Musical Instruments - Montagu, Jeremy (Rowman & Littlefield Publishers, 2007)
Origins and Development of Musical Instruments describes the creation, use, and development of musical instruments from the Old Stone Age to the present day. Musical instruments, from the simplest whistles to the most complex organs, conch trumpets to sousaphones, archers' and musical bows to violins and pianos, the most basic straw reeds to the modern MIDI systems, and pairs of stones struck together to synthesizers, are all described here by instrument collector and expert Jeremy Montagu. Montagu speculates on how these instruments originated in the earliest days of humanity and relates how they moved from one culture to another through history, all the while changing and developing until they became the instruments we know today. The book also surveys the present uses of instruments throughout the world. Each chapter is devoted to a different type of instrument. Intervals and additional sections enhance the volume with information on musicians, the Medieval Renaissance, the ideal accompaniment, archaeology, symbiotic and newly created instruments, classification of instruments, scales and music, and some of the problems of acoustics. This comprehensive volume is illustrated with over 120 photos capturing several hundred instruments from all over the world; many of them from the author's own collection of over 2,500 instruments. A copious bibliography of sources, three indexes, and a series of maps make this a priceless resource.